Experiences of Transgenders/Trans People in the Access to Comprehensive Mental Health in Córdoba, Argentina During the Period 2021-2023, from a Transfeminist-Latin American Approach (Palimpsesto, 2023)
The aim of this article is to analyze the access of the transgender/trans population to comprehensive mental health services, focusing on first level services and care for problematic substance use. The analytical division focuses on the incidence of comprehensive mental health services on the possibilities of labor inclusion of transgenders/trans people in the formal employment circuit. The analysis of the problem is carried out through a situated ethnography, relating the access to these devices from the perspective of the population and its agents during the period 2021-2023, in the city of Córdoba.
Keywords: comprehensive mental health; trans/transgender personas; accessibility